Salinity tolerance of three competing rangeland plant species: Studies in hydroponic culture. Issue 24 (12th November 2017) - Sagers, Joseph K.; Waldron, Blair L.; Creech, Joseph Earl; Mott, Ivan W.; Bugbee, Bruce
Abstract: Halogeton ( Halogeton glomeratus ) is an invasive species that displaces Gardner's saltbush ( Atriplex gardneri ) on saline rangelands, whereas, forage kochia ( Bassia prostrata ) potentially can rehabilitate these ecosystems. Salinity tolerance has been hypothesized as the predominant factor affecting frequency of these species. This study compared relative salinity tolerance of these species, and tall wheatgrass ( Thinopyrum ponticum ) and alfalfa ( Medicago sativa ). Plants were evaluated in hydroponics, eliminating the confounding effects of drought, for 28 days at 0, 150, 200, 300, 400, 600, and 800 mmol/L NaCl. Survival, growth, and ion accumulation were determined. Alfalfa and tall wheatgrass shoot mass were reduced to 32% of the control at 150 mmol/L. Forage kochia survived to 600 mmol/L, but mass was reduced at all salinity levels. Halogeton and Gardner's saltbush increased or maintained shoot mass up to 400 mmol/L. Furthermore, both actively accumulated sodium in shoots, indicating that Na + was the principle ion in osmotic adjustment, whereas, forage kochia exhibited passive (linear) Na + accumulation as salinity increased. This study confirmed the halophytic nature of these three species, but, moreover, discovered that Gardner's saltbush was as saline tolerant as halogeton, whereas, forage kochia was less tolerant. Therefore, factors other than salinity tolerance drive these species' differential persistence in saline‐desert ecosystems. Abstract : This study confirmed the halophytic nature of halogeton, Gardner's saltbush, and forage kochia, but moreover, discovered that Gardner's saltbush was as saline tolerant as halogeton, whereas, forage kochia was less tolerant. Therefore, factors other than salinity tolerance are driving these species' differential persistence in saline‐desert ecosystems.